Embedded autonomy states and industrial transformation - Evans, Peter B. 1944- (Princeton Univ. Press, 1995)
Evans starts with the idea that states vary in the way they are organized and tied to society. In some nations, like Zaire, the state is predatory, ruthlessly extracting and providing nothing of value in return. In others, like Korea, it is developmental, promoting industrial transformation. In still others, like Brazil and India, it is in-between, sometimes helping, sometimes hindering. Evans's years of comparative research on the successes and failures of state involvement in the process of industrialization have here been crafted into a persuasive and entertaining work, which demonstrates that successful state action requires an understanding of its own limits, a realistic relationship to the global economy, and the combination of coherent internal organization and close links to society that Evans calls "embedded autonomy.
Keywords: Computerindustrie; Industria de la computación - Política gubernamental - Corea (República); Industria de la computación - Política gubernamental - India; Industrias secundarias (economia); Industriepolitiek; Industriële ontwikkeling; Staat (politicologie); Politik; Computer industry -- Government policy -- Brazil; Computer industry -- Government policy -- India; Computer industry -- Government policy -- Korea (South); Industrial policy -- Brazil; Industrial policy -- India; Industrial policy -- Korea (South); Wirtschaftspolitik; Industrie; Brasil - Industria - Política gubernamental; Corea (República) - Industria - Política gubernamental; India - Industria - Política gubernamental; Brasilien; Indien; Südkorea